Passivity-based control for battery charging/discharging applications by using a buck-boost DC-DC converter (2018)
In this paper, a passivity-based control (PBC) theory is applied to control a battery energy storage system (BESS) under current control mode by employing a bidirectional buck-boost DC-DC converter. The proposed controller guarantees globally exponentially stability for the system under closed-loop conditions via proportional control design. An averaging model of the buck-boost DC-DC converter is employed to represent the dynamics of the system via port-Hamiltonian (pH) structure. Simulation results show that a unique control law can be used to the charging or discharging battery process. MATLAB/SIMULINK software is employed to validate the proposed control methodology. © 2018 IEEE.